Larval collectors network documents the spread of the invasive bivalve Pinctada radiata in the Mediterranean Sea - Júlia García-Colomé; Iris E. Hendriks; Isabel Abel-Abellán; Giorgio Aglieri; Peru Agueda; Natalia Aisa-Bravo; Elvira Álvarez; María P. Andrada-Nicolás; Irene Antón-Linares; Elisa Arroyo-Martínez; Carolina Audisio-Pacheco; Tatjana Bakran-Petricioli; et al. (Marine Environmental Research, 2026)

From loss to life: how empty Pinna nobilis shells enhance motile macroinvertebrate habitats in soft-bottom environments - Ana Fortič; Valentina Pitacco; Domen Trkov (Estuarine, Coastal and Shelf Science, 2026)

New records of marine biodiversity in the Mediterranean Sea (April 2026) - ARGYRO ZENETOS; FARES NASSER ABD EL-GWAAD; AHMED MOHAMED AL-BEAK; MOUNA ANTIT; YACOPO BALDACCHINO; CLAUDIO BARRÍA; ILIJA ĆETKOVIĆ; MAURIZIO COSTA; FABIO CROCETTA; NIKOLA ĐORĐEVIĆ; AMANI FITORI; BELLA S. GALIL; et al. (Mediterranean Marine Science, 2026)
This collective article presents new information about 18 species occurring in 12 Mediterranean countries from the Alboran Sea to the Levantine Sea. Five lessepsian species namely Erugosquilla massavensis, Syrnola fasciata, Plocamopherus ocellatus, Maritigrella fuscopunctata and Siganus javus have spread within 2025 to neighbouring MSFD areas. Another five are here reported as first country records [Polyandrocarpa zorritensis (Malta), Gonioinfradens giardi (Italy), Istiblennius meleagris (Egypt), Epinephelus fasciatus (Israel), Lophocladia trichoclados (Montenegro)]. Cladophora patentiramea has spread from the Levantine to the Aegean Sea, while Pinctada radiata has reached Granada, and Cádiz. The Atlantic fish Enchelycore anatina and Synodus synodus have expanded their distribution to Montenegro and Syria respectively. Three rare native species are reported for first time at country level, while a fourth (Mobula birostris) has made an appearance more than a century after its first Mediterranean record.

Climate-Driven Habitat Shifts in Brown Algal Forests: Insights from the Adriatic Sea - Daša Donša; Danijel Ivajnšič; Lovrenc Lipej; Domen Trkov; Borut Mavrič; Valentina Pitacco; Ana Fortič; Ana Lokovšek; Milijan Šiško; Martina Orlando-Bonaca (Journal of Marine Science and Engineering, 2026)
Brown algal forests (Cystoseira sensu lato) are key habitat-forming components of temperate rocky coasts but have experienced widespread decline across the Mediterranean Sea. This study investigates the current distribution and potential future shifts in brown algal forests across the Adriatic Sea under ongoing climate change. We combined non-destructive field-based mapping along the Slovenian coastline with remote-sensing products and spatial environmental predictors to model basin-wide habitat suitability. A multiscale geographically weighted regression (MGWR) framework was applied to account for spatial non-stationarity and to explicitly capture the fact that environmental drivers of habitat suitability operate at different spatial scales—an assumption that global models such as GAM or standard GWR cannot adequately address. Habitat suitability maps were generated for present-day conditions and projected under mid- and late-century climate scenarios. The results reveal pronounced latitudinal gradients, identify areas of ongoing canopy decline in the northern Adriatic, and highlight parts of the southern Adriatic as potential climate refugia. Overall, the study demonstrates a likely north–south contraction of suitable habitat for brown algal forests and underscores the value of multiscale spatial modelling for informing marine spatial planning, conservation prioritization, and climate-adaptive restoration under European policy frameworks.

Enhancing ex situ cultivation of Mediterranean Fucales: species-specific responses of Gongolaria barbata and Ericaria crinita seedlings to algal extracts - Ana Lokovšek; Martina Orlando-Bonaca; Edi Gljušćić; Andrea Bilajac; Ljiljana Iveša; Alberta Di Cave; Saverio Savio; Federico Ortenzi; Domen Trkov; Roberta Congestri; Annalisa Falace (Marine Environmental Research, 2025)

A half-century of nuclear research, education and training: Story of the JSI TRIGA reactor - Luka Snoj; Klemen Ambrožič; Loïc Barbot; Ljudmila Benedik; Arne Bratkič; Ivana Capan; Christelle Reynard-Carette; Vladimir Cindro; Dušan Čalič; Christophe Destouches; Benoit Geslot; Alireza Haghighat; et al. (Annals of Nuclear Energy, 2025)

Faunistic, ecological, and zoogeographical survey of heterobranch fauna in the Adriatic Sea: experiences from Slovenia - LOVRENC LIPEJ; ANA FORTIČ; DOMEN TRKOV; BORUT MAVRIČ; DANIJEL IVAJNŠIČ (Mediterranean Marine Science, 2025)
The heterobranch fauna recorded to date in the Slovenian part of the Adriatic Sea was reviewed and analysed in order to present an updated inventory. The ecological traits and zoogeographical affiliation of the recorded heterobranchs were also analysed. The new data revealed that the heterobranch fauna in the area consists of at least 157 species with the majority being nudibranchs (61.4%). The bulk of heterobranchs were considered as Atlanto-Mediterraneans. Heterobranch diversity was found to be significantly related to the number of sampling events. The spatial pattern of heterobranch species and their composition structure in parts of the study area were linked to specific human-impacted areas (HIAs) such as coastal wetlands, ports, and mariculture facilities. Better examination of less investigated environments, new sampling techniques, and citizen science involvement will doubtlessly increase the numbers in this checklist.

New records of rarely reported species in the Mediterranean Sea (March 2025) - JOSÉ CARLOS BÁEZ; OKAN AKYOL; ERNESTO AZZURRO; PIETRO BATTAGLIA; ANGEL BELMONTE-GALLEGOS; GEORGIOS CHRISTIDIS; FABIO CROCETTA; CEM DALYAN; YUNUS GÖNÜL; FABIO GRATI; SILVESTRO GRECO; CHRYSOULA GUBILI; et al. (Mediterranean Marine Science, 2025)
This collective study presents information on fifteen (15) species recorded across five countries (Greece, Italy, Slovenia, Spain, and Türkiye) and four (4) ecoregions, ranging from the Alboran Sea to the Aegean Sea. The recorded species belong to three phyla: Mollusca (3 species), Arthropoda (3 species), and Chordata (9 species). Among mollusks, Martadoris mediterranea is reported for the first time in the Aegean Sea at two different locations, while Opisthoteuthis calypso and Octopoteuthis sicula are newly recorded in the western Mediterranean. Regarding arthropods, Ocypode cursor is reported from the Tyrrhenian coast of Sicily, Pachygrapsus transversus is recorded for the first time in the Tyrrhenian Sea, and Cancer pagurus in the Sea of Marmara. Among chordates, Lobotes surinamensis and Zu cristatus are newly recorded in the Alboran Sea, while Callionymus fasciatus and Symphodus doderleini are reported from Slovenian coastal waters. Tripterygion delaisi and Gymnothorax unicolor are documented for the first time in the waters of the Sea of Marmara and Crete, respectively. Additionally, new records of rarely reported fish species include Arctozenus risso, Chromogobius zebratus, and Epinephelus aeneus in Turkish, Spanish, and Italian waters, respectively.

The coastal ichthyofauna of the Mediterranean coral reef: the case of Mljet National Park (Croatia, southern Adriatic Sea) - Lovrenc Lipej; Danijel Ivajnšič; Valentina Pitacco; Borut Mavrič; Domen Trkov; Petar Kružić (Frontiers in Marine Science, 2024)
The authors studied the structure of the coastal fish assemblage in a temperate coral reef within a marine protected area in order to provide a baseline information on the occurrence and temporal distribution of fish and to highlight the importance of the coral reef to ichthyofauna. The coastal fish assemblage was investigated at two sites in Veliko jezero (Mljet National Park) in the southern Adriatic Sea with a non-destructive SCUBA visual technique in the period from 2013 to 2021. Altogether, 38 fish taxa were recorded on the right bank (coral reef) and 36 species on the left bank. The presence of the coral reef at a depth range between 9 m to 12 m is the main factor differentiating the fish fauna in these two areas, which are otherwise governed by the same environmental factors. At the coral reef a decrease in fish diversity was discovered with a steady regression from 2013 to 2021.

Too Hot to Handle: Effects of Water Temperature on the Early Life Stages of Gongolaria barbata (Fucales) - Ana Lokovšek; Valentina Pitacco; Annalisa Falace; Domen Trkov; Martina Orlando-Bonaca (Journal of Marine Science and Engineering, 2024)
Gongolaria barbata plays a crucial role as a habitat-forming Fucales species in the Mediterranean Sea, thriving in shallow, sheltered coastal regions, where it exhibits optimal growth in a temperature range of 10 to 25 °C. In the northern Adriatic Sea, a semi-enclosed part of the Mediterranean, there has been a remarkable increase in seawater temperatures in recent decades, often exceeding 28 °C in summer. These high temperatures pose a significant threat to the vulnerable early life stages of G. barbata. This study delves into the effects of four temperatures (15, 18, 24, and 28 °C) on the growth of G. barbata over its first 16 days, closely monitoring mortality, deformities, and overall survival. Our experiments reveal that higher temperatures can result in deformities and increased mortality of germlings. Notably, a temperature of 28 °C resulted in the death of all germlings within the first week, whereas those exposed to 24 °C survived until the second week, albeit with significant deformities prior to death. In contrast, germlings cultivated at 15 and 18 °C exhibited normal development with minimal deformities. These results highlight the susceptibility of the early life stages of G. barbata to temperature-induced stress and provide valuable insights into the potential consequences of rising seawater temperatures in the Mediterranean.

Global warming scenarios for the Eastern Adriatic Sea indicate a higher risk of invasiveness of non-native marine organisms relative to current climate conditions - Branko Glamuzina; Lorenzo Vilizzi; Marina Piria; Ante Žuljević; Ana Bratoš Cetinić; Ana Pešić; Branko Dragičević; Lovrenc Lipej; Marijana Pećarević; Vlasta Bartulović; Sanja Grđan; Ivan Cvitković; et al. (Marine Life Science & Technology, 2023)

New records of rarely reported species in the Mediterranean Sea (July 2023) - DANIELE GRECH; EMANUELE ASCIUTTO; RIGERS BAKIU; PIETRO BATTAGLIA; CHAIMA BEN-GRIRA; ÖZNUR YAZILAN ÇAMLIK; ROBERTO CAPPUCCINELLI; LEILA CARMONA; SAHAR CHEBAANE; FABIO CROCETTA; ANDREA DESIDERATO; FILIPPO DOMENICHETTI; et al. (Mediterranean Marine Science, 2023)
This Collective Article presents new information about the occurrence of 23 marine taxa that belong to five Phyla: two Chlorophyta, one Annelida, six Mollusca, three Arthropoda, eleven Chordata (one Ascidiacea, one Elasmobranchii and nine Teleostei) and extending from the Western Mediterranean to the Levantine Sea. All these records were reported from nine countries from the western to the eastern Mediterranean Sea, with a broad biogeographical coverage as follows: Spain: first records of the sacoglossans Cyerce graeca and Placida tardyi for the Alboran Sea and first records of the nudibranch Marionia gemmii for the Mediterranean waters of Spain; first records of nudibranch Algarvia alba in the Mediterranean Sea. Italy: First report of the long-legged crab Paragalene longicrura, a further new Mediterranean record of the rare offshore rockfish Pontinus kuhlii, first documented record of the spiny butterfly ray Gymnura altavela in Sardinia (Tyrrhenian Sea), new record of the red‐spotted wrasse Lappanella fasciata from the Messina Strait, first documented record of the rarely observed brown moray Gymnothorax unicolor in the Ionian coast, first record of the colonial ascidian Botrylloides israeliensis, first record of the Morocco dentex Dentex maroccanus, first record of mottled shore crab Pachygrapsus maurus and of an adult specimen of barracudina Lestidiops sphyrenoides in the Adriatic Sea, and further new Mediterranean records of Ross worm Sabellaria spinulosa along the same coast. Tunisia: second record of smalleye squaretail Tetragonurus cuvieri from the African Mediterranean coast. Slovenia: first records of the sea slug Trapania graeffei and Melanochlamys wildpretii, with the last one also representing the northernmost finding of this species. Croatia: northernmost record of the endangered twaite shad Alosa fallax in the Adriatic coast. Albania: first records of the Mediterranean spearfish Tetrapturus belone. Türkiye: first record from the Aegean coasts for Türkiye of the green macroalgae Cladophora battersii and Valonia aegagropila. Israel: first record of the skeleton shrimp Caprella acanthifera in the Southeastern Mediterranean Sea. Syria: first record of the Smooth grenadier Nezumia aequalis from Syrian marine waters.

Coastal Fish Fauna in the Cystoseira s.l. Algal Belts: Experiences from the Northern Adriatic Sea - Lovrenc Lipej; Danijel Ivajnšič; Valentina Pitacco; Domen Trkov; Borut Mavrič; Martina Orlando-Bonaca (Journal of Marine Science and Engineering, 2023)
Cystoseira s.l. forests are recognised as important habitats which host diverse coastal fish assemblages. Many fish species use such habitats as feeding, breeding, and nursery grounds. Since the coastal fish community depends on the availability of dense macroalgal belts, the decline of these habitats in the Mediterranean Sea also affects the density of coastal fish species. We studied the coastal fish assemblage in Cystoseira s.l. forests in three consecutive years 2019–2021 in the Gulf of Trieste (Adriatic Sea). Data on coastal fish fauna were collected by visual counts conducted by SCUBA diving. Data on algal cover and habitat types were obtained by recording with a video camera. Similarities and differences in the fish community were analysed in terms of habitat and substrate preferences. A total of 34 species were recorded in Cystoseira forests. The results of the present study show that the different algal cover and associated depth gradient have different effects on the fish assemblage in coastal waters, affecting species composition and abundance. For many species, particularly labrids and sea breams, there is a decreasing temporal trend in frequency of occurrence and density. However, fish community trends can be used as a good “proxy” to evaluate the algal belt status. Our results indicate that rapid conservation and restoration actions are needed to stem the decline of Cystoseira s.l. forests.

New records of rare species in the Mediterranean Sea (December 2022) - FEDERICA MONTESANTO; MARCO ALBANO; DΕΝΙΖ AYAS; FEDERICO BETTI; GIOELE CAPILLO; MELIH ERTAN ÇINAR; MARIA CORSINI-FOKA; FABIO CROCETTA; ERTAN DAĞLI; CLAUDIO D’IGLIO; MARKOS DIGENIS; BRANKO DRAGIČEVIĆ; et al. (Mediterranean Marine Science, 2022)
This Collective Article presents information on 20 taxa belonging to five (5) Phyla: Cnidaria (2), Mollusca (8), Arthropoda (4), Echinodermata (1) and Chordata (5) recorded from the Alboran Sea to the Levantine Sea. These new records were found in seven (7) different ecoregions as follows: Alboran Sea: new record of the rare football octopus Ocythoe tuberculata in the harbour of Algeciras (Spain); Western Mediterranean Sea: first record of the isopod Arcturinella deltensis in the Ligurian Sea, and the third in the whole Mediterranean Sea; third Mediterranean site for the Muricidae Coralliophila ahuiri along the Italian coasts (Alghero); first and westernmost record of the goby Corcyrogobius liechtensteini from the Iberian Peninsula; new record of the sea slug Glaucus atlanticus from the coast of the Iberian Peninsula; first and easternmost record of Holothuria (Vaneyothuria) lentiginosa lentiginosa along the Italian coasts; Tunisian Plateau/Gulf of Sidra: seventh record of the oceanic squid Thysanoteuthis rhombus in Tunisia, and first for the Gulf of Gabes. Ionian Sea: second occurrence of the Atlantic tripletail Lobotes surinamensis in the Ionian Sea and first record from the Strait of Messina area; new record of the rare sea elephant Pterotrachea coronata from the Strait of Messina; Adriatic Sea: first record of a facies of football ascidian Diazona violacea in the South Adriatic Sea (Tremiti Island, Italy); two records of the sevengill shark Heptranchias perlo in Croatian waters after more than 70 years of absence of documented records in this area; first known occurrence of the nudibranch Jalonus hyalinus in Slovenian waters and also the first known occurrence of this species in the Adriatic Sea; first record of the nudibranch Okenia elegans in Slovenian waters; Aegean Sea: First record of the parasitic isopod Nerocila milesensis along Greek coasts (Crete island) as well as the second record worldwide; additional record of the brachyuran Paragalene longicrura collected from the Saronikos Gulf (Greece); first record of the siphonophore Rhizophysa filiformis in Greek waters as well as the second record of this species in the eastern Mediterranean basin; new record of the rare and protected angelshark Squatina aculeata along Turkish coasts; Levantine Sea: first record of the marine amphipod Caprella andreae in the Levantine Mediterranean shore of Israel, based on both morphological and molecular data; first occurrence of the cephalopod Tremoctopus violaceus along Turkish coasts, which confirms its presence in the north-eastern coasts of Turkey; record of a bloom of the thermophilic jellyfish Pelagia noctiluca in the north Levantine Sea.

Where and how - new insight for brown algal forest restoration in the Adriatic - Martina Orlando-Bonaca; Gilda Savonitto; Valentina Asnaghi; Domen Trkov; Valentina Pitacco; Milijan Šiško; Tihomir Makovec; Petra Slavinec; Ana Lokovšek; Saul Ciriaco; Mariachiara Chiantore; Sara Kaleb; et al. (Frontiers in Marine Science, 2022)
Several anthropogenic factors are responsible for the decline of Cystoseira sensu lato (hereafter Cystoseira ) forests along Mediterranean coasts. Some Cystoseira species are already regionally extinct, and their decline has been widely recorded. Sustainable and efficient techniques for the restoration of Cystoseira are needed. In this context, the objectives of this study were i) to analyse the reproductive traits of three populations of Gongolaria barbata from three nearby donor sites in the northern Adriatic Sea, assessing the differences in their reproductive potential and reproductive success; and ii) to evaluate the outplanting success in terms of the effectiveness of G. barbata restoration, in relation to the different donor and receiving sites (Miramare MPA and in front of the Marine Biology Station Piran - MBSP) and implemented methods ( ex situ and hybrid method combining a mesocosm cultivation and a suspended culture in the field). After 2 weeks of cultivation in mesocosms, half of the tiles with germlings were transported to the receiving sites and placed on suspended lantern nets (hybrid method), which were later (after 3 months) transferred to the seabed on concrete plates with protective cages. The remaining tiles were placed on the seabed on concrete plates with protective cages after a 4-week culture ( ex situ method). At both sites, lantern nets and plates were randomly placed at 3 m depth. Thallus length was measured monthly in each treatment. Seedlings in suspended culture showed lower performance at the Miramare MPA, most likely due to the unfavourable environmental conditions. The satisfactory results obtained at MBSP demonstrate the efficiency of the hybrid method and confirm its potential to reduce the cost and time required for cultivation. Since unpredictable climatic events pose the greatest threat to restoration performance, these challenges must be considered when establishing new restoration practices. Moreover, herbivore regulation is extremely urgent and should be planned and implemented on a larger regional scale.

New Alien Mediterranean Biodiversity Records (August 2022) - FRANCESCO TIRALONGO; OKAN AKYOL; SARA A.A. AL MABRUK; PIETRO BATTAGLIA; DAMLA BETON; BANU BITLIS; JOSEPH A. BORG; MARC BOUCHOUCHA; MELIH ERTAN ÇINAR; FABIO CROCETTA; BRANKO DRAGIČEVIĆ; Jakov DULČIĆ JDULČIĆ; et al. (Mediterranean Marine Science, 2022)
In this Collective Article on alien and cryptogenic diversity in the Mediterranean Sea we report a total of 19 species belonging to nine Phyla and coming from nine countries. Several of these records concern fish species, and of particular interest are the first records of: Terapon puta for Italian waters; Pteragopus trispilus from Malta; Plotosus lineatus from Cyprus; and the northernmost Mediterranean record of Lagocephalus sceleratus. The northernmost Mediterranean record was also reported for the sea urchin Diadema setosum. The portunid crab Thalamita poissonii was recorded for the first time in Libya. The copepod Pseudodiaptomus marinus was recorded for the first time in the Marmara Sea. The polychaete Branchiomma luctuosum was recorded for the first time from the Mediterranean coast of France. The alien anemone Diadumene lineata was recorded for the first time from Slovenia. The macroalgae Sargassum furcatum was recorded for the first time from Italy. The new Mediterranean records here reported help tracing abundance and distribution of alien and cryptic species in the Mediterranean Sea.

An Insight into the Feeding Ecology of Serranus scriba, a Shallow Water Mesopredator in the Northern Adriatic Sea, with a Non-Destructive Method - Ana Lokovšek; Martina Orlando-Bonaca; Domen Trkov; Lovrenc Lipej (Fishes, 2022)
Serranus scriba is a common member of the coastal fish community in the Adriatic Sea, but knowledge about its feeding ecology is scarce. The aim of this paper is to present new evidence about its food preferences and feeding habits. An innovative non-destructive method of fecal pellet analysis was used for this study. This method does not require sacrificing specimens and the fish can be released back into the sea alive after the laboratory work. The results demonstrated that S. scriba mainly preys on decapods, followed by polychaetes, isopods, fish, mollusks and swarming shrimps. The calculated index of trophic diversity (ITD) value of 0.89 indicates that it is an opportunistic feeder that feeds on a wide range of different prey. According to the calculated trophic level of 3.43, which is higher than that of other members of the community, S. scriba is also an important piscivorous predator. With age, S. scriba undergoes an ontogenetic shift. The proportion of crustaceans, gastropods and polychaetes decreases with age and body size, while the proportion of fish increases.

Factors Influencing Habitat Selection of Three Cryptobenthic Clingfish Species in the Shallow North Adriatic Sea - Domen Trkov; Danijel Ivajnšič; Marcelo Kovačić; Lovrenc Lipej (Journal of Marine Science and Engineering, 2021)
Cryptobenthic fishes were often overlooked in the past due to their cryptic lifestyle, so knowledge of their ecology is still incomplete. One of the most poorly studied taxa of fishes in the Mediterranean Sea is clingfish. In this paper we examine the habitat preferences of three clingfish species (Lepadogaster lepadogaster, L. candolii, and Apletodon incognitus) occurring in the Gulf of Trieste (Northern Adriatic). The results show that all three species have a cryptic lifestyle and are well-segregated based on their depth distribution and macro- and microhabitat preferences. L. lepadogaster inhabits shallow waters of the lower mediolittoral and upper infralittoral, where it occurs on rocky bottoms under stones. L. candolii similarly occurs in the rocky infralittoral under stones, but below the lower distribution limit of L. lepadogaster, and in seagrass meadows, where it occupies empty seashells. Such hiding places in seagrass meadows are also occupied by A. incognitus, which mostly occurs below the lower distribution limit of L. candolii. Despite the overlap of depth and macrohabitat, the probability of individuals of two species encountering each other or competing in the same habitat is low when the depth range is combined with the microhabitat preferences of these species.

Observations on the diet of the Starry skate, Raja asterias Delaroche, 1809 (Elasmobranchii: Rajidae) in the Adriatic Sea - SONJA SVIBEN; DOMEN TRKOV; BORUT MAVRIČ; PETAR KRUŽIĆ; LOVRENC LIPEJ (Mediterranean Marine Science, 2019)
Diet of immature specimens of the Starry skate (Raja asterias) was investigated in three different parts of the northern Adriatic Sea. Decapod crabs were found to be the skate’s primary food source, followed by teleost fish and cephalopods. An ontogenetic shift in the diet towards teleost fish was observed. No significant differences were noted comparing the diet of 22 females and 63 males, 81 juveniles and 4 adults and different size groups. The prey species preferences were different for the specimens feeding on the Italian side of the northern Adriatic, but nonetheless decapods remained the preferred food source.

A non-destructive method for assessing the feeding habits of coastal fish - DOMEN TRKOV; LOVRENC LIPEJ (Mediterranean Marine Science, 2019)
Studies on the feeding ecology of sympatric coastal species is important, especially in revealing different strategies to reduce competition. The aim of this study is to test the diet of littoral fish species with a non-destructive method, which does not necessitate the sacrifice of fish specimens. The clingfish Lepadogaster lepadogaster (Bonnaterre, 1788) was used to test this diet assessment method. Freshly caught specimens were delivered immediately to a specially designed box for collecting faecal pellets, supplied by an aerator. Clingfishes were left in the chambers for 24 hours to defecate. The pellets were carefully removed and fixed in 70% alcohol. The content of the pellets was analysed under stereomicroscope and prey items were determined and counted. The comparison with the existing studies showed similarity and consistency between their results, which proves the usefulness and applicability of the method for studying clingfish diet. The suitability of the proposed method was tested on related species L. candollei Risso, 1810, where all ingested prey items were also found and identified in faecal pellets, which confirms its effectiveness for diet analysis. A method of collecting faecal pellets immediately after defecation has proved to be more useful and effective than other nonlethal methods. After defecation, the specimens were released at the site where they were collected. Due to 100% survival as shown in this research, the proposed method is also suitable for studying the diet of rare and endangered fish species, and also coastal fish fauna in protected areas where traditional destructive sampling methods are not appropriate or allowed.

New Mediterranean Biodiversity Records (November 2018) - MEHMET BAKİ YOKEŞ; VASILIS ANDREOU; RIGERS BAKIU; SARA BONANOMI; JUDITH CAMPS; GEORGE CHRISTIDIS; FABIO CROCETTA; IOANNIS GIOVOS; ANDREA GORI; TEA JURETIĆ; SELAHATTİN ÜNSAL KARHAN; STELIOS KATSANEVAKIS; et al. (Mediterranean Marine Science, 2018)

New Mediterranean Biodiversity Records (July 2018) - NIKI CHARTOSIA; DIMITRIS ANASTASIADIS; HOCEIN BAZAIRI; FABIO CROCETTA; ALAN DEIDUN; MARIJA DESPALATOVIĆ; VINCENZO DI MARTINO; NIKOS DIMITRIOU; BRANKO DRAGIČEVIĆ; JAKOV DULČIĆ; FURKAN DURUCAN; DENIZ HASBEK; et al. (Mediterranean Marine Science, 2018)
In the present article, new records are given for 15 species (4 native and 9 alien and 2 cryptogenic), belonging to 6 Phyla (i.e. Chlorophyta, Ctenophora, Cnidaria, Mollusca, Arthropoda, and Chordata), from 10 Mediterranean countries: Morocco: the finding of the crab Callinectes sapidus represents the westernmost one of the species in the Mediterranean; Italy: first records of the nudibranch Polycera hedgpethi from the harbour of La Spezia, and first finding of the invasive ctenophore Mnemiopsis leidyi in the Fiora River; Tunisia: Caulerpa taxifolia var. distichophylla is recorded for the first time, showing an even wider distribution in the Mediterranean; Greece: the finding of the jellyfish Pelagia benovici represents the first record of the species in the Ionian Sea, while the finding of the smallscale codlet Bregmaceros nectabanus in the Ionian Sea is another interesting first report for the area; Malta: the cryptogenic scleractinian coral Oculina patagonica was recorded; Slovenia: the parasitic copepod Demoleus heptapus was recorded from a sixgill bluntnose shark, Hexanchus griseus; Croatia: the Lessepsian cephalaspidean mollusc Haminoea cyanomarginata is recorded for the first time from the area; Bulgaria: the Asian date mussel Arcuatula senhousia was recorded from the Black Sea; Cyprus: the Lessepsian gastropod Viriola sp. [cf. corrugata) was recorded for the first time from the area, while two decapod species were recorded also for the first time from Cyprus, i.e. the caridean shrimp Pasiphaea sivado and the anomuran Munida curvimana; Turkey: the acari Lohmannella falcata is recorded for the first time from Antalya and the Lessepsian fish Priacanthus sagittarius in the Levantine coasts of Turkey (off Hatay/Arsuz) showing that this species has extended its range in a very short time.